Application of infrared spectroscopy techniques for the assessment of quality and safety in spices: a review. Issue 7 (8th August 2020) - Kaavya, R.; Pandiselvam, R.; Mohammed, Mahadhir; Dakshayani, R.; Kothakota, Anjineyulu; Ramesh, S. V.; Cozzolino, Daniel; Ashokkumar, C.
Abstract: Adulteration of spices has been a major threat in the past decades as it decreases the quality and causes illness to humans. Testing of species is essential for evaluating the quality and safeguards the consumer against bogus activities. It is important to ensure the quality of spices throughout its value chain. Conventional techniques used to detect the quality and adulterations in spices are destructive nature, time-consuming, and do not suitable for online monitoring. Despite traditional methods, spectroscopy is an emerging technology; this has been substantiated to be the dynamic and progressive method in detecting the adulteration of species. It is a simple, rapid, and nondestructive analytical tool familiarized with the food industry in the detection of adulterants present in the food sample. This review paper focuses on the application of spectroscopy techniques in adulteration detection and the quality assessment of spices and herbs. The present paper would be a roadmap for the researchers and industries for the detection of adulteration more efficiently and it would take up on-line quality and safety control of spices, agricultural products and food in the future.